EVALUASI PELAKSANAAN PROGRAM JAMINAN KESEHATAN MASYARAKAT - Yulianda, Airine (Jurnal Ilmu Administrasi Negara, 2016)
Evaluation of Community Health Insurance Program. This study aims to investigate the implementation of the Community Health Insurance Program (Assurance) in the sub-district Puskesmas Rengat on Sipayung and the factors that affect implementation. This research uses qualitative descriptive method. Based on the evaluation of the implementation of the Community Health Insurance Program (Assurance) in District Rengat cases at health centers Sipayung basically not run optimally. Factors affecting among other things the lack of socialization and communication between program managers jamkesmas, lack of infrastructure, lack of availability of drugs in health centers as well as the slow Sipayung workers in providing health services.